2007
DOI: 10.1089/apc.2006.0138
|View full text |Cite
|
Sign up to set email alerts
|

Living with HIV But Without Medical Care: Barriers to Engagement

Abstract: This cross-sectional study examined factors associated with the receipt of HIV medical care among people who know their HIV status and are not newly diagnosed with HIV. Interviews were conducted with 1133 HIV-positive individuals between October 2003 and July 2005 who enrolled in 1 of 10 outreach programs across the country. The sample was predominantly non-white (86%), male (59%), and unstably housed (61%), with a past history of cocaine use (68%). Twelve percent had received no HIV medical care in the 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 34 publications
1
88
0
Order By: Relevance
“…Though retention and suppression are often treated separately in the literature, 11,[16][17][18][19][20]35,36 this study examined both measures by focusing on an impoverished, vulnerable prospective cohort of WOC. For these women, our findings suggest that retention and viral suppression were influenced by different factors, and that interventions seeking to improve retention may require program components and strategies that differ from interventions aiming to improve viral suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though retention and suppression are often treated separately in the literature, 11,[16][17][18][19][20]35,36 this study examined both measures by focusing on an impoverished, vulnerable prospective cohort of WOC. For these women, our findings suggest that retention and viral suppression were influenced by different factors, and that interventions seeking to improve retention may require program components and strategies that differ from interventions aiming to improve viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are numerous studies examining factors associated with retention in care or viral suppression, 11,[16][17][18][19][20] fewer examine both in a single study. 11,21 A few studies focus on women exclusively, but are more focused on HIV acquisition, 22 and none focus on WOC who are disproportionally affected by HIV/AIDS.…”
mentioning
confidence: 99%
“…The presence or absence of integrated care might differentially impact care access in other settings. 11,22 Alternatively, other factors among KPNC patients might lower their risk of mortality despite missing some visits. For example, homelessness is associated with decreased access to medical care, but is not a significant issue among our patients.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Some studies using different age ranges for analysis found no difference in linkage in younger adults. 35,[43][44][45] However, combining published data from these studies (Table 1), we estimate that 62% of newly diagnosed HIV-infected adolescents and young adults in the United States link to care within the first 6-12 months.…”
Section: Linkage To Carementioning
confidence: 99%